PENGEMBANGAN MEDIA PEMBELAJARAN GEOGRAFI MENGGUNAKAN ARTICULATE STORYLINE PADA MATERI ATMOSFER KELAS X MERDEKA 2 DI SMA NEGERI 1 TANJUNG MORAWA T.A 2023/2024 - Br Butar-Butar, Ester Luvita; Arif, Muhammad (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to: (1) Produce media using articulate storyline as a medium for learning geography on atmospheric material, (2) Find out the feasibility of media using articulate storyline on atmospheric material as learning media, (3) Find out students' responses to the development of articulate storyline media on material atmosphere. The research method used is the development research method and the development model is 4D (Define, Design, Development, Disseminate). The data used in this research are qualitative data and quantitative data. The data that has been previously obtained from the validator can then be used as a reference for revising the product, so as to produce a viable product. The subjects in this research were 36 students in class X Merdeka 2 SMA Negeri 1 Tanjung Morawa. Based on data analysis, the researcher stated that the learning media using Articulate Sotryline in the Atmosphere material developed by the researcher met the criteria for learning media, namely valid, practical and effective.